Can we be certain that storage duration of transfused red blood cells does not affect patient outcomes? - Trivella, M; Stanworth, S; Brunskill, S; Dutton, P; Altman, D (BMJ Publishing Group, 2019)
Red cell transfusion is one of the most common forms of medical intervention in hospitals. Optimal practice continues to be defined through randomised trials, with evidence then pooled in meta-analyses. Prolonged storage of red blood cells is associated with cellular and biochemical changes,1 2 and this has led to numerous studies exploring whether the age of red blood cells might influence clinical outcomes. Establishing clinical consequences of storage effects on red blood cells would be of major importance for blood transfusion services. The four most recent randomised trials (ABLE,3 RECESS,4 INFORM,5 and TRANSFUSE6 ; box 1) analysed nearly 30 000 patients who received transfusions, reporting neither benefit nor harm from cells with different storage durations. These results should provide adequate reassurance that storage duration has no clinical impact. Several older and smaller trials,7-21 as well as recent meta-analyses,22-24 have reported similar conclusions. However, clinical, methodological, and statistical problems may have affected the analysis and interpretation of trial results. Here, we discuss the difficulties in analysing the trials and suggest some solutions.